Problems in plan revision. - Aboyade, Ojetunji; Nigerian Institute of Social and Economic Research (Ibadan, Nigerian Institute of Social and Economic Research, 1965)
This volume is a reprint from The Nigerian Journal of Economic and Social Studies, vol. 7 no. 2, July 1965. It examines the circumstances under which any economic plan revision can be justified.
lje 14/3/19
Arch.
Keywords: Economic plans; Nigeria